Мethods of ensuring data protection against brute force cryptographic attacks - Rudyk O. F. (НТУ "ДП", 2024)
One of the most common threats is brute force attacks. Brute force is a technique used in cybersecurity to crack encrypted messages or passwords by systematically trying all possible combinations until the correct one is found. This method is based on the assumption that the encryption algorithm used is known, but the key or password is unknown. The use of these methods is relevant when solving security aspects of problems in sources using the algorithms described in. In the case of using a brute-force method to decrypt text protected by a symmetric key, the level of complexity of information disclosure can be relatively low, especially if the key is short or not sufficiently complex. If an 8-bit key is used, there are 2^8, or 256, possible keys. Therefore, it will take at most 256 tries to find the correct key, with a 50 percent chance of finding the right key after half of the tries.
Keywords: криптографічне забезпечення; метод атак; метод перебору